Plant growth promotion of the forage plant Lupinus albus Var. Orden Dorado using Pseudomonas agronomica sp. nov. and Bacillus pretiosus sp. nov. added over a valorized agricultural biowaste - Robas Mora, Marina; Fernández Pastrana, Vanesa M.; Oliva, Laura Luna Gutiérrez; Lobo, Agustín Probanza; Jiménez Gómez, Pedro A. (Frontiers in Microbiology, 2023)
Introduction The overexploitation of natural ecosystems and the evolution of climate change currently force us to design new strategies for more sustainable agronomic uses. The recovery of plant residues, as an alternative to agrochemicals, can help alleviate these problems, for example, through its use for the synthesis of biofertilizers. In this work, the effect of the organic fertilizer matrix ORGAON® from the valorization of horticultural waste is tested, to which two strains of bacteria (and their consortium) are added (SAICEU11T identified as Bacillus pretiosus and SAICEU22T identified as Pseudomonas agronomica), selected for their demonstrated ability to promote plant growth (PGPB), on the lupine forage plant (Lupinus albus). Methods For the synthesis of the biofertilizer, both strains were added to the ORGAON® organic matrix separately, until reaching a final optical density (OD) of 0.5 McFarland in each case in the irrigation matrix. As a control, sterile ORGAON® (ORGAON®st) was used, also supplemented with the PGPB strains and a chemical fertilizer widely used in agronomy (Chem-F). With these treatments, a 6-week experiment was started under controlled laboratory conditions and on agricultural substrate, to recreate field conditions as accurately as possible. All the tests were carried out with 9 repetitions and 3 replicates of each treatment. After harvest, the improvements on the following biometric variables were studied for each treatment: total weight (Weight_T, g), shoot weight (Weight_S, g), root weight (Weight_R, g), number of leaves (Leaves, No.), shoot length (Length_S), root length (Length_R) and number of secondary roots (Roots, No.). Likewise, the identification of the tested strains and their description as new species was carried out. For this, they were studied from the phenotypic point of view (Transmission electron microscopy (TEM), metabolic profile, PGP activities, fatty acid profile and Matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF)) and genotypic (sequencing of the main housekeeping genes and sequencing of the whole genome, genomic characteristics (dDDH and ANI) and phylogenetic analysis). Results and discussion After the statistical analysis of the results, it is shown that the individual addition of both strains on the ORGAON® and ORGAON®st organic matrix improve certain biometric variables. In the case of the SAICEU11T (Bacillus pretiosus) strain, the variables root weight (Weight_R, g), total weight (Weight_T, g) and length of the plant, and number of secondary roots (Roots, No.) significantly improve, while in the case of the strain SAICEU22T (Pseudmonas agronomica), a significant improvement of root length (Length_R) and number of secondary roots (Roots, No.) is demonstrated. On the other hand, the genotaxonomic analysis showed that both species have not been described to date. The identification based on the main housekeeping genes, show that for the Bacillus strain (SAICEU11T) the sequence similarity of the 16S rRNA was 100%, gyrB 92.69%, rpoB 97.70% and rpoD 94.67%. For the Pseudomonas strain (SAICEU22T) the results were 100% for 16S rRNA, 98.43% for rpoD and 96.94% for gyrB. However, in both cases, the dDDH and ANI values, as well as the phylogenetic analysis, show that both species are below the species threshold, which would support the hypothesis that both are new species, in line with the chemotaxonomic results obtained by MALDI-TOF spectrometry and fatty acid profile. To verify the biosafety in their handling and release into the natural environment, we have ruled out the presence of genes that encode virulence factors or resistance to antibiotics, concluding that they are suitable for use in the field to improve the yield of crop plants. Type strains are SAICEU11T (= DSM 114702T = CECT30674T) for Bacillus pretiosus and SAICEU22T (= DSM 114959T = CECT30673T) for Pseudomonas agronomicae.